Estudo sobre os antecedentes da satisfação, lealdade e desempenho no mercado brasileiro de e-commerce - Tiago Aroeira de Pinho Tavares (2015)
Consumer satisfaction and loyalty are issues of utmost importance to marketing studies. In addition, the achievement of performance goals is presented as a matter of great importance for organizations. In this context, it is observed that the emerging of internet revolutionizedmarkets and caused significant changes in people's habits and behaviors, due to its capability to influence social relations and provide new opportunities for interaction and transactional efficiency among businesses and consumers. As a result, the e-commerce emerged as asuitable tool for market globalization and expansion while delivering significant benefits to consumers, businesses and society. The continued growth of the amount of purchases made over the Internet, increased annual sales value of this business model as well as the constant evolution in the number of consumers of online stores show the market relevance of electronic commerce. The significant increase of the published marketing studies related to the e-commerce subject shows the academic interest in contributing to the maturation of scientific knowledge inherent to the specificities of virtual stores. In this context, this study aims to measure and propose a model that shows the relationship between the factors of quality prior to the satisfaction, satisfaction itself, loyalty and performance in the Brazilian ecommerce, from the analysis of the top ten virtual stores in Brazil: Mercado Livre Brasil, Americanas.com, Buscapé, Dafiti.com.br, Bomnegócio.com, OLX, NetShoes, ShoppingUOL, Casas Bahia e Groupon Brazil. The method used was a quantitative research conducted through data collection from a non-probabilistic sample of 1.087 respondents from all regionsof Brazil. The analyzed data were analyzed regarding the characteritics of the sample, atypical observations (outliers), linearity and normality prior to the evaluation of the measurement model and the structural equation model (SEM). The central technique employed was Partial Least Squares Path Model (PLS-PM). The research model analysis was based on scales developed by Anderson; Swaminathan (2011) and Parasuraman et al (2005) and enabled the understanding of the relationships between the constructs analyzed. The study showed, from the analysis of a main model and an alternative model, which aspects are able to explain morethan 60% of the causes of satisfaction among consumers. The aspects are: Trust, Variety, Client Network, Purchase Interface, Adaptability and Commitment to Customers. In addition, it was observed that the Privacy and Commitment to Customers are able to explain about 50% of the determination of Trust. Moreover, more than 50% of loyalty causes can be explained by inertia and satisfaction. Finally, it became clear that the Loyalty positively influences the performance measurements. This research contributes to the expansion and deepening of studies regarding the connection through satisfaction, loyalty and performance in the specific context of electronic commerce.